Modelling the Process of Forming Economic Competence in Students of Polytechnic College in the Situation of Informatization of Education - O A Puchkova; G A Kruchinina (Peoples' Friendship University of Russia (RUDN University), 2011)
The model of forming the economic competence of the students of polytechnic college is described in the article. The attention is focused on the use of the information and communication technologies in teaching economics. The results of the experimental work on enhancing the level of forming economic competence of students of professional education are given.